77=17+6x

Simple and best practice solution for 77=17+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 77=17+6x equation:


Simplifying
77 = 17 + 6x

Solving
77 = 17 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
77 + -6x = 17 + 6x + -6x

Combine like terms: 6x + -6x = 0
77 + -6x = 17 + 0
77 + -6x = 17

Add '-77' to each side of the equation.
77 + -77 + -6x = 17 + -77

Combine like terms: 77 + -77 = 0
0 + -6x = 17 + -77
-6x = 17 + -77

Combine like terms: 17 + -77 = -60
-6x = -60

Divide each side by '-6'.
x = 10

Simplifying
x = 10

See similar equations:

| 6n-6=6-5n | | 35x+x=3x+14 | | 6u-7=3 | | [2t-4]=8 | | 2(5x-8)-5(3x+5)=-5x | | 7x+8=3x+29 | | -2x+4=x+7 | | -6(6+5a)=-66 | | (-3)-2(x+6)=-5 | | -1=-.5x+2 | | 9w+33=3(w-9) | | 825+3.25x=8.20x | | X-(-2)=-6 | | -7y+5=4 | | 900=5e^9x | | (14x-5)+13x=180 | | -15=15q-50-5p | | (8x-1)(5x+1)=0 | | (5k+3)(k-2)=0 | | -6(3+2k)=-78 | | 5(5r+5)=-100 | | (2x+8)(x-3)=154 | | H=16t(7-t)+10 | | 3t^6*3t^2= | | 6c=11 | | -46=-6x+2 | | Sin^2(x)-sin(x)-1=0 | | 6(x-4)+10=2x-12 | | 115x+25+10x=1400 | | 11=-3-x | | 4v=7 | | 2(m-3)-(2m+6)= |

Equations solver categories